2003
DOI: 10.1088/0741-3335/45/12a/016
|View full text |Cite
|
Sign up to set email alerts
|

Overview of physics basis for ITER

Abstract: ITER will be the first magnetic confinement device with burning DT plasma and fusion power of about 0.5 GW. Parameters of ITER plasma have been predicted using methodologies summarized in the ITER Physics Basis (1999 Nucl. Fusion 39 2175). During the past few years, new results have been obtained that substantiate confidence in achieving Q 10 in ITER with inductive H-mode operation. These include achievement of a good H-mode confinement near the Greenwald density at high triangularity of the plasma cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 76 publications
0
63
1
Order By: Relevance
“…It is a well known fact from ITER confinement database studies [26] that for densities near and beyond the Greenwald value the confinement observed no longer agrees with the scaling and the corresponding H98 values drop significantly below unity. Pellet fuelling experiments performed at JET and AUG showed that in ITER relevant scenarios a density regime beyond values accessible with gas puffing can be accessed but there is no further improvement in the energy confinement [27].…”
Section: Confinement At High Densities and Limitation Of The Iterh98pmentioning
confidence: 87%
“…It is a well known fact from ITER confinement database studies [26] that for densities near and beyond the Greenwald value the confinement observed no longer agrees with the scaling and the corresponding H98 values drop significantly below unity. Pellet fuelling experiments performed at JET and AUG showed that in ITER relevant scenarios a density regime beyond values accessible with gas puffing can be accessed but there is no further improvement in the energy confinement [27].…”
Section: Confinement At High Densities and Limitation Of The Iterh98pmentioning
confidence: 87%
“…[24][25][26][27][28][29][30][31][32]. Both DW and BM instabilities can exist in this range of R=L n and both resistive and inertial effects are important, and therefore we expect the behaviour of the SOL to change remarkably in these wide intervals of parameters.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The relative importance of each mode, however, is still unclear, and non-linear simulations of edge and SOL turbulent dynamics have addressed both instabilities. The SOL region, in particular, is characterized by a wide range of density gradients and resistivities, [24][25][26][27][28][29][30][31][32] allowing the interplay between E Â B convection and curvature effects to change considerably, depending on the plasma scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The design criteria of the ITER plasma shape with κ = 1.7 and δ = 0.33 (at 95% flux surface) are based on a conservative regime that is well established in present experiments [14]. More extreme variations of flux surface shaping were investigated with the experiment TCV (Tokamakà Configuration Variable) which is able to achieve configurations up to κ = 3 and δ = ±0.5 [15].…”
Section: Introductionmentioning
confidence: 97%
“…Criteria for design of new magnetized plasma experiments for fusion research like ITER are primarily based on empirical scaling laws for the energy confinement time [14]. First-principle based transport models still require reference to experimental scalings, and are validated mainly only for core plasmas excepting the pedestal region [5].…”
Section: Introductionmentioning
confidence: 99%